Meningkatkan Intention To Use Aplikasi Mobile JKN Melalui Perceived Usefulness Dan Attitude Towards Use Sebagai Variabel Intervening (Studi pada Pengguna Aplikasi Mobile JKN Segmen Pekerja Penerima Upah Badan Usaha di Wilayah BPJS Kesehatan Cabang Serang) - Wahyudi, Wawan; Mukhsin, Moh.; Nupus, Hayati (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2021)
This study aims to examine and analyze the effect of perceived ease to use and subjective norms on intention to use with perceived usefulness and attitude towards use as an intervening variable (a study on users of the JKN mobile application segment of workers receiving corporate wages in the Serang Branch of BPJS Kesehatan). The data collection methods used are library research and field studies by distributing questionnaires to 190 users of the JKN mobile application for the segment of workers who receive wages for business entities in the Serang Branch of BPJS Kesehatan using proportional random sampling techniques. The data analysis technique used is Structural Equation Modeling (SEM) with SmartPLS software. The results of this study indicate that perceived ease to use has a negative and insignificant effect on intention to use; subjective norm has a positive and significant effect on intention to use; perceived ease to use has a positive and significant effect on perceived usefulness; perceived ease to use has a positive and significant effect on attitude towards use; subjective norm has a positive and significant effect on perceived usefulness; Subjective norm has a positive and significant effect on attitude towards use; perceived usefulness has a positive and significant effect on intention to use; and attitude towards use has a positive and significant effect on intention to use.